Imigração e colonização: a colônia Getúlio Vargas/RS em fotografias (1908-1954) - Mokfa, Patricia Lilian (2019)
Addressing the process of immigration and colonization from photographic images has revealed particularities about the representation of / and about the colonial nuclei. In the present study, we analyze the photographic images of the Getúlio Vargas colony, part of the Erechim colony, nowadays Getúlio Vargas municipality, located in the north of Rio Grande do Sul, from 1908 to 1954. The time frame established by the research corresponds to the period when immigrants and migrants began to settle in the colony; Then the process of colonization and development takes place. It is the analysis of a set of thirty nine photographs that are under the custody of the Getúlio Vargas Historical and Geographic Archive, whose theme is the changes and permanence of the rural and urban space of the Getúlio Vargas colony and its subjects, settlers and immigrants who populated this place. The thematic cut is justified by the relevance and lack of studies in this line and the availability of this photographic collection. Starting from the concept of representation of Chartier (1991), the objective is to understand how the photographers represented the formation of Getúlio Vargas colony with respect to the photographed spaces, the settlers' installation in their lots, the correlation between colonization and railroad, organization of the urban space of the colony in the early twentieth century. The research allows us to understand that the records made by photographers build narratives, in photographic images, about the colonization of Getúlio Vargas over more than fifty years and leave for posterity the representations of this process. Photographs gain document and research source status to retrieve the past, multiply their eyes, and discover what life was like back then. He presented the various ethnicities and how they operated in the everyday universe through their cultural and social practices in the midst of their resistances, conflicts. We sought to reflect on the representations of the colonization process in photography, inspired by the experiences and adaptation needs of immigrants who settled there, as a resource for visual representation, for the creation of memories and for historical and social significance.